2008
DOI: 10.1080/02680930801987794
|View full text |Cite
|
Sign up to set email alerts
|

Finding an identity and meeting a standard: connecting the conflicting in teacher induction

Abstract: This article has the apparently contradictory aims of describing a discourse of new teachers that is at odds with the policy-derived competence-based discourse of the professional standard for teachers, and of also seeking to find some points of connection that may help start a dialogue between policy and research. The experience of new teachers is conceptualised as personal stories of identity formation with a clear emotional-relational dimension and a sense of self and intrinsic purpose in which others, espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Whilst this is not a new area of study, it is a particularly apposite time to look at this process, not only because of the performative agenda outlined above, but because we are now seeing a generation of newcomers to the profession who (given that most people enter the profession in their early to mid-twenties), are increasingly likely to be themselves the product of the performative school era. As noted earlier, some studies have noted the limitations and contradictions of formalised 'competence benchmarking' of professionalism (Harrison, 2007, McNally et al, 2008 A 25 year-old at the time of this study (the average age of the teachers taking part) would have started school around the time of the introduction of National Curriculum in England (1989), so spending their entire schooling within a school system undergoing profound and ongoing reform. They will have seen numerous curricular requirements, guidance, strategies and initiatives introduced and implemented, they will have been taught by teachers whose performance in that role was managed in fundamentally different ways -and they would almost certainly have been in schools through a number of Ofsted inspections (an experience reported by many as having a significant impact on pupils as well as teachers (Jeffrey & Woods, 1997;Mansell, 2007).…”
Section: The Performative Teacher?mentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst this is not a new area of study, it is a particularly apposite time to look at this process, not only because of the performative agenda outlined above, but because we are now seeing a generation of newcomers to the profession who (given that most people enter the profession in their early to mid-twenties), are increasingly likely to be themselves the product of the performative school era. As noted earlier, some studies have noted the limitations and contradictions of formalised 'competence benchmarking' of professionalism (Harrison, 2007, McNally et al, 2008 A 25 year-old at the time of this study (the average age of the teachers taking part) would have started school around the time of the introduction of National Curriculum in England (1989), so spending their entire schooling within a school system undergoing profound and ongoing reform. They will have seen numerous curricular requirements, guidance, strategies and initiatives introduced and implemented, they will have been taught by teachers whose performance in that role was managed in fundamentally different ways -and they would almost certainly have been in schools through a number of Ofsted inspections (an experience reported by many as having a significant impact on pupils as well as teachers (Jeffrey & Woods, 1997;Mansell, 2007).…”
Section: The Performative Teacher?mentioning
confidence: 99%
“…Some critics, however, have questioned the difficulty of quantifying the assessment of such a complex, nuanced aspect of teaching (Harrison, 2007, McNally et al, 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Hatch, White and Capitlelli's (2005) exploration of the first year of school teaching found that interactions with colleagues 'validate and challenge [teachers'] experiences and emerging hypotheses and connects [them] with a wide range of related research ideas and information'(p329), indicating that interactions are an important site for reconstructing learning. Informal 'on the spot' support is also particularly significant in early career learning (Eraut, 2004;McCormick et al, 2006;McNally et al, 2008). Most of the case study trainees recounted ways in which interactions with their workplace mentors had supported their learning.…”
Section: Workplace Affordances For Learningmentioning
confidence: 99%
“…The importance of interactions with and support from workplace colleagues, particularly through the establishment of relationships which provide emotional support (Hobson et al, 2008;McNally, Blake, Corbin & Gray, 2008), and the giving of feedback (for example: McCormack, Gore & Thomas, 2006), are recurrent themes in beginning and early career school teacher learning research. Hatch, White and Capitlelli's (2005) exploration of the first year of school teaching found that interactions with colleagues 'validate and challenge [teachers'] experiences and emerging hypotheses and connects [them] with a wide range of related research ideas and information'(p329), indicating that interactions are an important site for reconstructing learning.…”
Section: Workplace Affordances For Learningmentioning
confidence: 99%
“…These are emulated in Jonathan's story. Furthermore, Dugas (2016) and McNally et al (2008) contend that where new teachers prioritise being accepted by pupils yet equally want to have authority within the classroom, this leads to 'these two desired entities being at odds with one another' (Dugas, 2016, p. 26). This may well be one of the reasons that participants in this research felt behaviour to be so influential on risk-taking, the perceived negative outcomes possibly transpiring from the odds felt between wanting to be accepted and having authority in the classroom.…”
Section: Pupil Behaviourmentioning
confidence: 99%